Time Management Assistance in Developing Superior Human Resources - Sopanah, Ana; Rusdianti, Imanita Septian; Sulistyan, Riza Bahtiar; Khasanah, Midhatul (TGO Journal of Community Development, 2025)
This study aims to improve the effectiveness of employee time management through training and mentoring at PT Kasih Jaya Sejahtera, Malang Regency. The method used was a qualitative approach with data collection techniques in the form of in-depth interviews with company owners, operational workers, and HR managers, as well as field observations from January to March 2025. The results of the activities showed an increase in employee ability to set work priorities, adherence to schedules, and efficiency in completing daily tasks. In addition, unique implementations such as the "Daily Focus Zone" system and daily digital monitoring emerged as innovations in time management practices. The discussion of the results indicates that the training and mentoring not only impacted individual behavior changes but also strengthened a disciplined and collaborative work culture within the company environment. These findings align with previous studies that emphasize the importance of time management in HR development and increasing organizational productivity. Despite limitations in the duration of the activities and the scope of participants, the results show great potential for the sustainability of similar programs in the future.